Aggressive Angiomyxoma: A Rare Perineal Mass - Ozsoy, Mehmet Sait; Colapkulu, Nuray; Gapbarov, Aman; Ekinci, Ozgur; Gunduz, Nesrin; Toksoz, Ayse Nur; Alimoglu, Orhan (International Journal of Human and Health Sciences (IJHHS), 2019)
Aggressive angiomyxoma (AAM) is a rare tumour that usually occurs in females at reproductive ages and affects pelvic region. We herein report a case of perineal AAM to conribute to the literature about pathological features and clinical outcomes of this tumour. A 36 year old female with no history of chronic diseases presented to our hospital with a nontender perineal mass. The mass was present for two years and it first appeared during pregnancy. She underwent surgery for local resection. The histology of the mass was consistent with AAM and multifocal extention into surgical margins was observed. With immunohistochemical staining the tumor was positive for desmin, CD31, CD34, ER and PR; poorly focal positive for SMA and negative for S-100. Ki67 was less than 1%. Due to surgical margin positivity she had a second operation. After the resection with clear margins, patient showed no signs of reccurence for 7 months. Resections with positive surgical margins were mostly concluded as reccurent with wide time range and reccurence rates, extended surgical resection is gold standard for management of this tumour. International Journal of Human and Health Sciences Vol. 03 No. 03 July’19. Page: 172-174